Pengembangan Bisnis Toko Kue dengan Pendekatan Analisis SWOT dan Analisis Prospektif - Shidqi Syauqi; Totok Pujianto; Efri Mardawati (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2022)
Business growth in Indonesia is currently growing very rapidly. Business competition is becoming increasingly stringent and requires business actors to continue to innovate. Aisyah Cake Shop as a newly operating business must be able to compete with other business actors. So that a business development strategy is needed that can provide changes in the future. Therefore, efforts to develop a business development strategy at Aisyah Cake Shop then use the SWOT analysis method approach and the prospective analysis method. The SWOT analysis method can identify internal and external business conditions and provide strategic recommendations based on existing conditions based on internal factors (strengths and weaknesses) and external factors (opportunities and threats) at Aisyah Cake Shop. The use of prospective analysis can provide an overview of strategy formulation by involving decision makers (stakeholders) based on the possibilities that may occur in the future. This study aims to formulate and determine strategies that can be applied to deal with conditions in the future. The results of the preparation of the business development strategy which are the main priorities for implementation are recruiting new workers, consistently implementing quality control in the production process and monitoring and evaluating raw materials.